El estilo de Max Weber. Sobre su participación en política y sobre el modo científico de escribir sociología - Morcillo Laiz, Álvaro (El Colegio de México, 2015)
During the last two and a half years of his life, Max Weber wrote letters that could be used to write a sociology of the Central European intelligentsia during the wars. Rather than discussing Weber’s encounters with the most renowned writers —Thomas Mann, Hugo von Hofmannsthal— and musicians —that of Richard Strauss, among several composers and conductors— of his time, this article discusses three more conventionally Weberian topics, which are nonetheless insufficiently understood: first Weber’s involvement, that and of some of his students, like Georgy Lukaçs, in politics at the end of World War I. Second, Weber’s writing style, which has been fre-quently decried, but that actually represents his attempt to overcome a challenge that had become important for his own project as a university professor. This is the third topic of the article: how Weber intended to found academic sociology as a disci-pline that should combine empirical facts, the historical past, and institutions, on theone hand, with the use of models, or ideal-types, as propounded by the Austrian School, on the other hand. To Weber’s short spell at the University of Vienna in 1918 corresponds an intellectual achievement as mediator between economy and sociology that has rested too long in oblivion.